The Effect of Diffuse Radiation on Ecosystem Carbon Fluxes Across China From FLUXNET Forest Observations - Deng, Xiaoqing; Zhang, Jing; Che, Yunfei; Zhou, Lihua; Lu, Tianwei; Han, Tian (Frontiers in Earth Science, 2022)
Aerosol loading and cloud cover can alter the composition of radiation reaching the Earth’s surface and affect the ecosystem’s carbon cycle. In this study, we established an empirical model of the diffuse radiation fraction (Kd) based on a clearness index (Kt) to obtain the Kd of four FLUXNET forest sites in China. We focused on the relationships among the Kd, photosynthetically active radiation (PAR), light-use efficiency (LUE) and gross primary productivity (GPP) through mechanistic analysis. The relationships between carbon fluxes (including GPP, ecosystem respiration (ER), and net ecosystem exchange (NEE)) and the Kd were explored. Furthermore, we investigated the influence of environmental factors on carbon fluxes. The results showed that the Kd models were accurate in estimating Kd (R2= 0.88-0.93). Overall, the GPP first increased and then decreased with increasing Kd. When Kd< Ko (Ko, the diffuse radiation fraction corresponding to the maximum value of GPP), the direct PAR decreased as Kd increased, while the diffuse PAR increased rapidly. At this stage, the diffuse fertilization effect led to an increase in GPP. When KoKdiff-max, the diffuse PAR began to decrease, and the reduction in the superimposed direct PAR caused the GPP of the canopy to drop rapidly. The LUE of the vegetation canopy was higher under diffuse light conditions than under direct light. Furthermore, with an increase in the Kd, the negative value change of the NEE was consistent with the GPP, but the ER was less affected by the Kd. Finally, the impact of temperature (TA) and vapor pressure deficit (VPD) on the GPP was unimodal, and the impact on the NEE was U-shaped. In addition, latent heat (LE) had a significant positive effect on GPP and NEE. Our study emphasized the relationship between the change in PAR composition and the Kd, as well as its impact on the carbon fluxes change, which is highly important to the study of carbon neutralization.